Robust γ-TiAl Dual Microstructure Concept by Advanced Electron Beam Powder Bed Fusion Technology - Reith, Marcel; Franke, Martin; Körner, Carolin (Crystals, 2023)
The dual microstructure concept for gamma titanium aluminides (γ-TiAl) processed via electron beam–powder bed fusion (PBF-EB) provides a huge potential for more efficient jet turbine engines. While the concept is feasible and the mechanical properties are promising, there are still some challenges. For an industrial application, the heat treatment window has to match the conditions in industrial furnaces. This study shows how the required heat treatment window can be achieved via advanced PBF-EB technology. Through using an electron beam with 150 kV acceleration voltage, the difference in aluminum between the designed aluminum-rich and aluminum-lean regions of the part is increased. Moreover, the aluminum content within each of these regions, respectively, is more homogenous compared to the 60 kV acceleration voltage. This combination provides a heat treatment window of 25 °C, enabling the industrial application of the dual microstructure concept for γ-TiAl.
CRIS-Team Scopus Importer:2024-12-16
Keywords: acceleration voltage; additive manufacturing; aluminum evaporation; beam characteristics; dual microstructure; electron beam powder bed fusion; titanium aluminide